Assessing the Impact of Internet of Things (IoT) Devices on Research and Education: Opportunities, Challenges, and Prospects in Nigeria - Olatoye, Adebola Aderemi (PT Mattawang Mediatama Solution, 2025)
Abstract This study investigates the extent to which IoT devices are being adopted in Nigerian tertiary institutions, with specific attention to their potential, constraints, and future implications. The study was guided by four objectives: to explore the opportunities IoT offers for enhancing teaching, learning, and research; to identify major challenges associated with its implementation in the Nigerian context; to evaluate the impact of IoT on the efficiency and outcomes of academic activities; and to highlight the future prospects and trends in IoT for transforming education and research in Nigeria. A mixed-methods approach was adopted, involving quantitative data from 360 respondents and qualitative insights from 12 key stakeholders interviewed across selected institutions nationwide. The findings reveal that IoT devices are increasingly being used to improve instructional delivery, personalize student learning, and enhance data collection for research. However, the study also identifies critical challenges including inadequate digital infrastructure, high cost of IoT systems, limited technical expertise, and the absence of clear national or institutional policies. Despite these challenges, respondents expressed strong optimism about the future role of IoT in enabling smart campuses, AI-driven learning environments, and innovative research collaboration. The study concluded that while the integration of IoT into Nigerian education and research is still in its formative stage, its transformative potential is evident. To fully realize this potential, there should be strategic investments in infrastructure, comprehensive training programmes, policy formulation, and inclusive implementation strategies are required. The study recommended a collaborative, future-oriented approach involving government, institutions, and industry stakeholders to ensure that IoT becomes a sustainable driver of academic excellence and national development. Keywords: Digital Innovation, Educational Technology, Internet of Things, Research, Smart Campus